On the axiological potential of textbooks for German language courses in the era of “liquid modernity”. A preliminary study report - Jaroszewska, Anna (Papers in Linguistics, 2025)
Setting the undertaken reflection in the context of Zygmunt Bauman’s “liquid modernity” and the thesis of the inseparability of language and culture, the article draws attention to an underexplored research direction in glottodidactics, namely non-linguistic goals of education. Emphasizing the importance of educational goals and the rank of the corresponding social competencies, the article focuses on the contemporary functions of school and roles of language teachers. This leads to formulating a universal canon of values and asking about the axiological potential of school textbooks for German as a second language in this regard. This question is answered by referring to the results of the author’s own research into the content layer of 94 textbooks approved for use in Polish secondary comprehensive and technical schools after 1989. In addition to fulfilling its cognitive and reporting function, the article-report is a harbinger of in-depth research on the possibility of implementing a module of education for values and through values in foreign language lessons.